(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
As the rate of information exchange accelerates, it becomes more difficult to control the process, to determine whether a particular message is justified or not. In such circumstances, the concepts of media education, media literacy, and media culture become extremely relevant. Gulom Mirzayev, press secretary and advisor on information policy issues of the director of the National Center for Human Rights of the Republic of Uzbekistan, reflects on this topic. -The new, 2025 year began with somewhat disturbing events that directly concern humanity’s right to use truthful and unbiased information. Instagram Facebook and Instagram have issued a statement saying that internet platforms controlled by Mark Zuckerberg,